Multilayer fuzzy control of multivariable systems by passive decomposition - Gregov, Alexander E. (Zielona Góra: Uniwersytet Zielonogórski)
The paper considers the problem of multilayer fuzzy control of multivariable systems. Some relevant definitions and theorems are given. Multilayer fuzzy control algorithms, based on passive decomposition of the original system into layers, are presented and illustrated by numerical examples.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka